1971
DOI: 10.1007/bf02531523
|View full text |Cite
|
Sign up to set email alerts
|

Liver phospholipids of rats fed a choline‐deficient diet supplemented with choline or methionine

Abstract: The low amount of arachidonic acid in the total phospholipids in the liver of rats fed a standard type of choline-deficient diet was corrected by either choline or methionine, which also increased food intake. Choline increased the content of this fatty acid in the phosphatidyl ethanolamine but not in the phosphatidyl choline. Methionine increased both the amount of phosphatidyl choline and its content of arachidonic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Moreover, methionine can be made de novo from betaine or methyltetrahydrofolate (Finkelstein and Martin, 1986). Therefore, the PC/PE ratio was decreased gradually over 3 months in MCD-wild-type mice as compared with acutely (over 3 days) in CD-Pemt 2/2 mice (Beare-Rogers, 1971;Lyman et al, 1973;Yost et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, methionine can be made de novo from betaine or methyltetrahydrofolate (Finkelstein and Martin, 1986). Therefore, the PC/PE ratio was decreased gradually over 3 months in MCD-wild-type mice as compared with acutely (over 3 days) in CD-Pemt 2/2 mice (Beare-Rogers, 1971;Lyman et al, 1973;Yost et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Brassica crops are important in global agriculture and oil production. High concentrations of erucic acid (C22:1) in the seed of oil-yielding Brassica species have been reported to be nutritionally undesirable ( Badawy et al 1994 , Beare-Rogers 1971 , Gopalan et al 1974 ). Therefore, a major objective for breeding is to identify and apply genetic resources to produce low erucic acid (LEA) (<2%) seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Increased biological half-lives of the PE subfractions from choline deficient rats suggested that the conversion of PE to PC was impaired possibly because of limited availability of methionine methyl groups for methylating the PE. The possibility that methionine might play an active role in determining the liver PC composition of choline-deficient rats was indicated by Beare-Rogers (18) who recently reported that supplementary methionine was more effective than choline for increasing the liver PC arachidonic acid in rats fed a cholinedeficient diet.…”
Section: Introductionmentioning
confidence: 99%